2007
DOI: 10.1007/s00125-007-0846-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the gene encoding the voltage-dependent Ca2+ channel CaV2.3 (CACNA1E) are associated with type 2 diabetes and impaired insulin secretion

Abstract: Aims/hypothesis Glucose-stimulated insulin secretion is dependent on the electrical activity of beta cells; hence, genes encoding beta cell ion channels are potential candidate genes for type 2 diabetes. The gene encoding the voltage-dependent Ca 2+ channel Ca V 2.3 (CACNA1E), telomeric to a region that has shown suggestive linkage to type 2 diabetes (1q21-q25), has been ascribed a role for second-phase insulin secretion. Methods Based upon the genotyping of 52 haplotype tagging single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
(50 reference statements)
0
28
1
Order By: Relevance
“…10 Subsequently, it was demonstrated that polymorphisms in the gene encoding Ca V 2.3 associate with type 2 diabetes and impaired insulin secretion. 11 In apparent conflict with these findings, we were unable to detect the message for Ca V 2.3 in RNA isolated from human islets (ref. 4 and Amisten S, personal communication).…”
contrasting
confidence: 43%
“…10 Subsequently, it was demonstrated that polymorphisms in the gene encoding Ca V 2.3 associate with type 2 diabetes and impaired insulin secretion. 11 In apparent conflict with these findings, we were unable to detect the message for Ca V 2.3 in RNA isolated from human islets (ref. 4 and Amisten S, personal communication).…”
contrasting
confidence: 43%
“…These findings are somewhat difficult to interpret, since mice of various ages (12-50 weeks) were used without appropriate age-matching or discrimination between male and female animals. The concept is nevertheless intriguing, as several studies have since linked variants in the gene encoding Ca v 2.3 channels to impaired glucose homeostasis in human T2DM patients [66][67][68]. Most notably, the region on chromosome 1q21-25, where the human Ca v 2.3 gene is located, has been linked to young-onset T2DM in Pima Indians [67].…”
Section: Pathophysiological Implicationsmentioning
confidence: 98%
“…Ca v 2.3 R-type Ca channel) in β-cells is controversial, and some studies indicate their absence in human islets (Braun et al, 2008; Yang and Berggren, 2005b), but there is evidence for association of Ca v 2.3 polymorphisms with impaired insulin secretion and development of type-2 diabetes (Holmkvist et al, 2007). They appear to play a role in second-phase insulin secretion by mobilizing insulin reserve granules to the readily releasable pool in mice.…”
Section: Mouse Models Of Altered Ca Channelsmentioning
confidence: 99%